2022
DOI: 10.3390/ijms23063242
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological and Molecular Features of Secondary Cancer (Metastasis) to the Thyroid and Advances in Management

Abstract: Secondary tumours to the thyroid gland are uncommon and often incidentally discovered on imaging. Symptomatic patients often present with a neck mass. Collision tumours of secondary tumours and primary thyroid neoplasms do occur. Ultrasound-guided fine-needle aspiration, core-needle biopsy, and surgical resection with histological and immunohistochemical analysis are employed to confirm diagnosis as well as for applying molecular studies to identify candidates for targeted therapy. Biopsy at the metastatic sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 115 publications
0
6
0
Order By: Relevance
“…TNM staging, which illustrates an association between mortality and nodal spread, is widely assessed to classify disease stage 19 . In thyroid staging, TNM also considers patient age 20 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TNM staging, which illustrates an association between mortality and nodal spread, is widely assessed to classify disease stage 19 . In thyroid staging, TNM also considers patient age 20 .…”
Section: Discussionmentioning
confidence: 99%
“…17,18 TNM staging, which illustrates an association between mortality and nodal spread, is widely assessed to classify disease stage. 19 In thyroid staging, TNM also considers patient age. 20 Another system that endocrinologists widely prefer is the MACIS evaluation system, 21 described by the Mayo Clinic.…”
Section: Discussionmentioning
confidence: 99%
“…Fine-needle aspiration cytology (FNAC) is the first choice for patients with suspected metastatic thyroid cancer. FNAC is simple and easy to perform, and it is the best method for preoperative diagnosis (9). A multi-institution study report on FNAC showed that 87% of TM patients could be diagnosed with thyroid malignancy by FNAC, and 93% of them could be specifically diagnosed with TM (14).…”
Section: Diagnosis Of Metastatic Thyroid Carcinomamentioning
confidence: 99%
“…The majority of patients with metastatic RCC to the thyroid have widely metastatic disease at time of detection, but a small percentage have oligometastatic spread to the thyroid alone. 5 In this subset of patients with RCC confined to the thyroid gland, thyroidectomy offers improved outcomes. Prior studies have demonstrated that thyroidectomy improves 1-year survival rates from 35% to 55% and increases overall survival from 12 to 36 months.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, metastatic disease portends a poor prognosis in RCC. The majority of patients with metastatic RCC to the thyroid have widely metastatic disease at time of detection, but a small percentage have oligometastatic spread to the thyroid alone 5 . In this subset of patients with RCC confined to the thyroid gland, thyroidectomy offers improved outcomes.…”
Section: Introductionmentioning
confidence: 99%